Caught between Solidarity and Hesitation: The 3/11 Earthquake and Theatre in Japan - Morihiro Niino (Critical Stages, 2012)
In Japan after the 3/11 earthquake, the determination for solidarity and the sense of hesitation became the two key features which characterized the contrast between artists in the most affected north-east part of Japan called Tohoku and Tokyo, which also shook very hard but has undergone comparatively small damages. Those in Tohoku had to overcome the initial shock accompanied by the sense of inanity before starting their struggle to explore new routes of communication and new forms of representation to share their horrendous experiences. On the other hand, those in Tokyo were faced with the difficult task of choosing the appropriate moral stance in commenting upon the disaster and its effects. Morihiro Niino discusses several artists to elucidate this contrast. (Editor)